O impacto do programa institucional de bolsa de iniciação à docência nos egressos de licenciatura em letras - inglês da Universidade Federal do Oeste do Pará. - AGUIAR, Alessandra Lima (Universidade Federal do Oeste do Pará, 2023)
The Institutional Grant Programme for Teaching Initiation (Pibid) has been an object of much research in the field of education. It was created with the purpose of improving initial teacher education by providing student teachers with an early contact with mentor teachers and schools. The investigation reported in this dissertation aimed to describe the impacts of the programme on three former TEFL undergraduate students of the Federal University of Western Pará (Ufopa). Moreover, it attempted to verify whether or not the activities that these undergraduates engaged in through the programme enabled them to improve their proficiency in English and helped them in their preparation towards becoming teachers of English. Dewey’s (2010) experiential learning and discussions by Romanowski (2007), Gatti (2010), Saviani (2009), Leffa (2001), Gimenez (2002) and Lima (2011) guided the investigation. It was characterized as a qualitative case study, and was supported by bibliographical research and data collected through a questionnaire and interviews. All three subjects hold an English as a foreign language teaching licence and a teaching position in maintained schools in the Amazon region. The results include a description of the activities that were developed by the three former Pibid grant holders from August 2012 to December 2014, and the main impacts of the programme on them: the realization that the pursuit of a teaching career was the best choice available for them and that embracing it was a decision made on the basis of self-identification with it as a result of their participation in the programme. In conclusion, we are inclined to believe that Pibid was beneficial to these teachers not only in terms of English proficiency and teaching strategies development, but also in helping them make an informed decision about the teaching career.